2019
DOI: 10.1210/jc.2018-02638
|View full text |Cite
|
Sign up to set email alerts
|

Mifepristone Treatment in Four Cases of Primary Bilateral Macronodular Adrenal Hyperplasia (BMAH)

Abstract: ContextPrimary bilateral macronodular adrenal hyperplasia (BMAH) is a rare form of adrenal Cushing syndrome conventionally treated with adrenalectomy. Medical treatment is often reserved for patients not eligible for surgery. However, to date there have been few studies about the efficacy of mifepristone for the treatment of BMAH associated with hypercortisolism.ObjectiveTo describe a series of patients with hypercortisolism due to BMAH treated with mifepristone from multiple medical practices.DesignWe retrosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…In line with our case series, there have been other reports of symptom management benefits with the use of mifepristone in patients with hypercortisolism prior to surgery. 13 , 35 - 37 Additionally, in Case 3, the pituitary tumor became visible during the interval period of medical therapy, allowing more targeted surgery, which may increase the likelihood of long-term remission. Mifepristone has been shown to increase ACTH levels.…”
Section: Discussionmentioning
confidence: 99%
“…In line with our case series, there have been other reports of symptom management benefits with the use of mifepristone in patients with hypercortisolism prior to surgery. 13 , 35 - 37 Additionally, in Case 3, the pituitary tumor became visible during the interval period of medical therapy, allowing more targeted surgery, which may increase the likelihood of long-term remission. Mifepristone has been shown to increase ACTH levels.…”
Section: Discussionmentioning
confidence: 99%
“…Unilateral adrenalectomy has recently been proposed as an alternative in selected patients, with some advocating for the removal of the larger gland, especially in older patients [ 23 ]. Recently the use of mifepristone has also been proposed [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mifepristone, administered 300 mg daily over 6 months, led to a significant reduction in insulin resistance as measured and an improvement in Beck’s Depression Inventory scores and Cushing’s Quality of Life scores in most patients [ 107 ]. In the same year, other authors showed that mifepristone was able to induce an improvement in cardiometabolic parameters as early as 2 weeks after treatment initiation in 4 patients with BMAH, who also experienced an amelioration of glycemic control and hypertension as well as weight loss [ 108 ]. Overall, the possible use of mifepristone as a treatment of adrenal mHC for patients with impaired glucose metabolism is hindered by its adverse events (abnormal vaginal bleeding, edema and potential hypocortisolism).…”
Section: Medical Therapy Of Mild Hypercortisolismmentioning
confidence: 99%